Kajian Pengelolaan Effluent Treatment Plant (ETP) PT. Wilmar Nabati Indonesia Padang dan Potensi Pemanfaatan Lumpur IPAL - Nur, Ansiha; Jingga, Rara Purnama; Dzakiyyah, Nadiyah (Dampak, 2024)
The Effluent Treatment Plant (ETP) at PT. Wilmar Nabati Indonesia (PT. WINA) processes wastewater from crude oil (CPO) production activities, as well as serving as a domestic office, workshop, security, quality control, and Niagara equipment washing facility. ETP PT. WINA has a processing capacity of 382 m3 per day. The processing unit at ETP PT. Wilmar Nabati Indonesia is made up of a carrier channel, fat trap, Niagara, ceramic reservoir, equalization tank, chemical reactor alum, cavitation air floatation (CAF) machine, accident tank, filter press, sequencing batch reactor (SBR), reservoir tank, sand filter, oil removal, and carbon filter. The objectives of this research are to evaluate the operation and maintenance of ETP PT. WINA in accordance with the Minister of Environment of the Republic of Indonesia's regulation No. 5 of 2014, as well as to investigate the potential use of sludge from ETP PT. WINA processing that is safe to use and does not have a negative impact on the environment or human health. Operations and maintenance at PT. WINA are addressed by SOP-WINA-ETP-13-001 to SOP-WINA-ETP-010. The quality of wastewater treatment at PT. WINA's ETP has met the quality standards established by the Minister of Environment's Regulation No. 5 of 2014 Attachment XXI concerning Wastewater Quality Standards for the Cooking Oil Industry, and the effluent of PT. WINA's ETP is suitable for discharge into water bodies, namely the sea. Although the ETP effluent has met the quality standards and is suitable for discharge into water bodies, the sludge produced from PT. WINA's wastewater treatment installation has not been optimally utilized and has caused environmental problems. One alternative recommendation that can be implemented is to utilize the sludge as a raw material for paving blocks that meet the SNI-03-0691-1996 standard. Keywords: wastewater, efluen standards, Effluent Treatment Plant (ETP), paving blocks, PT. Wilmar Nabati Indonesia (PT WINA) ABSTRAKEffluent Treatment Plant (ETP) PT. Wilmar Nabati Indonesia (PT. WINA) berfungsi sebagai tempat untuk pengolahan air limbah yang bersumber dari kegiatan proses produksi pengolahan minyak mentah (CPO), domestic office, workshop, security, quality control dan pencucian alat niagara. ETP PT. WINA memiliki kapasitas pengolahan 382 m3/hari. Unit pengolahan di ETP PT. Wilmar Nabati Indonesia terdiri dari saluran pembawa, fat trap, niagara, ceramic reservoir, ekualisasi tank, chemical reactor alum, cavitation air floatation (CAF) machine, accident tank, filter press, sequencing batch reactor (SBR), reservoir tank, sand filter dan oil removal, dan carbon filter. Tujuan penelitian ini berupa melakukan kajian terhadap evaluasi operasional dan perawatan ETP PT. WINA berdasarkan regulasi Peraturan Menteri Lingkungan Hidup Republik Indonesia No. 5 Tahun 2014 dan melakukan kajian potensi pemanfaatan lumpur hasil pengolahan ETP PT. WINA yang aman digunakan sehingga tidak menimbulkan dampak negatif terhadap lingkungan dan kesehatan manusia. Operasional dan pemeliharaan pada PT. WINA mengacu kepada SOP-WINA-ETP-13-001 sampai SOP-WINA-ETP-010. Kualitas air hasil pengolahan air limbah di ETP PT. WINA sudah memenuhi standar baku mutu berdasarkan Peraturan Menteri Lingkungan Hidup No. 5 Tahun 2014 Lampiran XXI tentang Baku Mutu Air Limbah untuk Industri Minyak Goreng, dan efluen ETP PT. WINA layak dibuang ke badan air yaitu laut. Meskipun efluen ETP sudah memenuhi baku mutu dan layak dibuang ke badan air, akan tetapi lumpur yang dihasilkan dari instalasi pengolahan air limbah PT. WINA belum dimanfaatkan secara optimal dan menimbulkan masalah lingkungan. Salah satu rekomendasi alternatif yang bisa diterapkan adalah memanfaatkan lumpur tersebut sebagai bahan baku untuk paving block yang sesuai standar SNI-03- 0691-1996. Kata kunci: air limbah, baku mutu, Effluent Treatment Plant (ETP), paving block, PT. Wilmar Nabati Indonesia (PT WINA)